2012
DOI: 10.1007/s11999-012-2545-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Minimally Invasive Total Knee Arthroplasty Improve Isokinetic Torque?

Abstract: Background Less invasive dissection of the extensor apparatus, one of the aspects of minimally invasive surgical (MIS) TKA, might result in less reduction of postoperative quadriceps strength. However, it is unclear whether MIS is associated with less strength reduction. Questions/purposes We asked whether knee strength (extensor or flexor torque) would be greater in patients having a MIS TKA compared with patients having a standard TKA and whether knee scores, alignment, ROM, tourniquet and operating times, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Others reported that the extent of quadriceps injury inflicted while performing knee arthroplasty correlates with postoperative knee extensor strength in the early postoperative course after knee arthoplasty [31][32][33]. Therefore, an MIS may be advantageous although no benefit for longer term recovery has been seen [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Others reported that the extent of quadriceps injury inflicted while performing knee arthroplasty correlates with postoperative knee extensor strength in the early postoperative course after knee arthoplasty [31][32][33]. Therefore, an MIS may be advantageous although no benefit for longer term recovery has been seen [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Before testing, patients completed a 10-minute warm-up on a stationary bicycle, and if needed, they were allowed to perform individual dynamic stretching and jumping. The isokinetic testing protocol was based on the protocol described by Liebensteiner et al 23 All tests were administered by the same researcher, who followed a standardized method for measuring peak extension and flexion torque using an isokinetic dynamometer (Con-Trex MJ; CMV AG). The testing protocol consisted of concentric quadriceps and hamstring contractions.…”
Section: Methodsmentioning
confidence: 99%
“…The testing protocol consisted of concentric quadriceps and hamstring contractions. 23 The patients started with the noninjured leg and performed 4 repetitions at an angular velocity of 60 deg/s. Angular velocity was automatically prescribed and controlled by the Con-Trex testing device software.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the results of our MIS versus standard TKA population were published in terms of other outcome parameters: WOMAC scores, knee extensor/flexor torque, radiographic outcome and tourniquet/operating time [ 12 ]. We found WOMAC score, knee extensor and flexor strength to have equal results, and leg axis, component positioning and tourniquet/operating time in MIS patients to even be slightly inferior.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings of static alignment are in good agreement with the valgus kinematics during gait (dynamic alignment) observed in the current study. The slightly inferior component positioning and whole leg alignment in MIS TKA were attributed to the limited surgical access [ 12 ].…”
Section: Discussionmentioning
confidence: 99%